ASSESSING GESTATIONAL DIABETES RISK: THE ASSOCIATION OF ABDOMINAL SUBCUTANEOUS FAT THICKNESS IN FIRST TRIMESTER AND GLUCOSE CHALLENGE TEST AT 24-28 WEEKS - Anwar, Adila; Akbar, Amina; Afroze, Sadaf; Tabasam, Shakra; Sheeba, Shahnaz; Ghana Shahid (Journal of Ayub Medical College Abbottabad, 2025)
Background: Gestational diabetes mellitus (GDM) is a common complication during pregnancy, affecting approximately 3–4% of expectant mothers. This condition increases the risk of postpartum diabetes in mothers and obesity in their children. Moreover, GDM is linked to a higher incidence of infections, pre-eclampsia, eclampsia, and large-for-gestational-age infants, all contributing to perinatal morbidity. This study aimed to examine the association between GDM and abdominal subcutaneous fat thickness (ASFT), with the specific objective of determining a predictive ASFT cut-off value for GDM. Methods: This study was conducted at the Obstetrics and Gynaecology Departments of Pakistan Air Force Hospital, Kamra, and Pakistan Air Force Hospital, Islamabad, between December 2023 and May 2024. The cohort included 288 pregnant women aged 21–35 years, none of whom had diabetes, a history of smoking, hypertension, or metabolic syndrome. Pre-pregnancy body mass index (BMI) and weight gain were recorded, and ASFT was measured via ultrasound. Between 24 and 28 weeks of gestation, participants underwent a 75 g oral glucose tolerance test (OGTT). Data analysis was performed using ROC curve analysis and logistic regression via IBM SPSS version 23.0. Results: Of the 288 participants, 52 (18.05%) were diagnosed with GDM. The mean maternal ASFT was 2.2±0.4 cm, with statistically significant differences observed between the GDM and non-GDM groups (p<0.05). An ASFT threshold of 2.1 cm demonstrated a sensitivity of 76.25% and specificity of 92.57% in predicting GDM. Conclusion: Maternal ASFT measured by ultrasound in the first trimester is a reliable predictor of GDM risk in the second trimester. This parameter may serve as a useful supplementary diagnostic tool for assessing early risk of GDM.